2021
DOI: 10.21511/ppm.19(1).2021.30
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a new paradigm of anti-money laundering: The experience of Ukraine

Abstract: The increase in the level of money laundering is associated with digitalization and technification of all spheres of society, the globalization of financial markets, the consequences of quarantine measures caused by the COVID-19 pandemic, and the new ways of committing money laundering crimes. The paper aims to identify the peculiarities of anti-money laundering activities in Ukraine and outline approaches to increase the effectiveness of combating money laundering in the country. The current state of the prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…Moreover, while Fletcher (2020) emphasizes Bitcoin, Zerzan (2009) emphasizes value cards, online banking and payments, digital currencies and mobile money. Finally, the study of (Vitvitskiy et al , 2021) concurred with Lester and Roth (2007) on the notion that the lack of sufficient training for AML/CFT professionals leads to an increase in criminal activities. And Further contribution is made by Raza et al (2020) stating that unemployment and internet access among youth exacerbate issues related to money laundering and terrorist financing.…”
Section: Literature Reviewmentioning
confidence: 68%
See 3 more Smart Citations
“…Moreover, while Fletcher (2020) emphasizes Bitcoin, Zerzan (2009) emphasizes value cards, online banking and payments, digital currencies and mobile money. Finally, the study of (Vitvitskiy et al , 2021) concurred with Lester and Roth (2007) on the notion that the lack of sufficient training for AML/CFT professionals leads to an increase in criminal activities. And Further contribution is made by Raza et al (2020) stating that unemployment and internet access among youth exacerbate issues related to money laundering and terrorist financing.…”
Section: Literature Reviewmentioning
confidence: 68%
“…Indeed, Stack's (2015) study even agrees with Hendriyetty and Grewal (2017) that money laundering effects government revenues, but through facilitating tax evasion and corruption. Furthermore, Bartlett (2002) believes that money laundering has generally negative effects on economic competitiveness, particularly the productive sectors, whiereas Vitvitskiy et al (2021) observed that money laundering makes developing countries become more vulnerable to economic breakdown than developed countries.…”
Section: Causes Of Money Laundering and Terrorist Financingmentioning
confidence: 99%
See 2 more Smart Citations
“…Bukhtiarova et al (2020) note that to ensure a high level of financial security and, accordingly, stability of the financial system, the level of deshadowing of the economy and, therefore, effective financial monitoring becomes important, which is primarily aimed at implementing measures to combat money laundering. This issue is extremely relevant for Ukraine, which is confirmed by the study of Vitvitskiy et al (2021), who found that the consequences of increasing money laundering are the formation of a significant budget deficit, reduced social funding and lower living standards, which negatively affects the state of the financial system's stability.…”
Section: Literature Reviewmentioning
confidence: 91%